Determining the effects of Hyperoside as a protective agent against to testicular damage (Annals of Medical Research, 2021)
Aim: The aim of this study is to evaluate the possible beneficial effects of hyperoside (HYP) in the mitigation of torsion detorsion (TD)-induced testicular oxidative damage. Materials and Methods: For this purpose, Wistar Albino rats were grouped (n=6 in each group) as sham, TD and TD+HYP groups. HYP was administered at 50 mg/kg dose p.o for 1 week. Torsion was created by twisting the spermatic cord clockwise by 720 degrees. The detorsion model was made by restoring the spermatic cord. Tissue oxidative and antioxidative stress parameters were measured according to biochemical methods to evaluate oxidative damage in testis. Results: In particular, the oxidative stress parameters we measured were found to be significantly increased compared to the sham group in TD group depending on the TD model, but showed a significant decrease depending on the HYP treatment (p0.05). In addition, it was observed that the antioxidative parameters decreased significantly in the TD group, while this decrease effectively changed in the TD+HYP group. Conclusion: Considering the current results, HYP therapy is thought to be useful in alleviating TD-induced oxidative damage in the testicles.
Keywords: Hyperoside; testis; torsion detorsion; oxidative stress